Women’s contribution in understanding how topoisomerases, supercoiling, and transcription control genome organization - Martin, Laura; Neguembor, Maria Victoria; Cosma, Maria Pia (Frontiers in Molecular Biosciences, 2023)
One of the biggest paradoxes in biology is that human genome is roughly 2 meters long, while the nucleus containing it is almost one million times smaller. To fit into the nucleus, DNA twists, bends and folds into several hierarchical levels of compaction. Still, DNA has to maintain a high degree of accessibility to be readily replicated and transcribed by proteins. How compaction and accessibility co-exist functionally in human cells is still a matter of debate. Here, we discuss how the torsional stress of the DNA helix acts as a buffer, regulating both chromatin compaction and accessibility. We will focus on chromatin supercoiling and on the emerging role of topoisomerases as pivotal regulators of genome organization. We will mainly highlight the major breakthrough studies led by women, with the intention of celebrating the work of this group that remains a minority within the scientific community.